Treecreeper Drone: Adaptive Mechanism for Passive Tree Trunk Perching - Haichuan Li; Shane Windsor; Basaran Bahadir Kocer (Advanced Intelligent Systems)
Collecting detailed information from trees via hovering with an aerial robot is both energetically inefficient and often infeasible in dense forest canopies. Perching on trees offers a promising solution by enabling prolonged observations with reduced energy consumption. To overcome perching location limitations, in this article, a bird‐inspired passive perching mechanism specifically optimized for vertical tree trunks is proposed. Similar to the tail action of treecreepers (Certhiidae family) when perching on vertical tree trunks, the proposed aerial robotic platform perches on tree surfaces using a main clawed gripping mechanism combined with a supporting “tail” mechanism featuring arrays of embedded microspines. To cope with the complex curvature of tree trunks, adaptive elastic joints that allow the mechanism to passively contact the tree's surface are introduced. By incorporating the region of attraction for the mechanism, the aerial platform is designed to be more reliable during perching maneuvers by adjusting angular movement, thereby defining suitable initial velocities and accelerations for achieving stable equilibrium. The proposed system is validated in a motion capture environment using vertical trunks with diameters ranging from 40 to 220 mm, and further demonstrates in outdoor perching tests. Results confirm the feasibility of dynamic perching on vertical tree trunks under realistic forest conditions.